"E-like" ascospore excision mutants in Neurospora tetrasperma resistant to either p-DL-fluorophenylalanine or methyl benzimidazol-2-y1 carbamate - J. P. Ardizzi; A. M. Srb (Fungal Genetics Reports, 1981)
"E-like" ascospore excision mutants in Neurospora tetetrasperma resistant to either p-DL-fluorophenylalanine or methyl benzimidazol-2-y1 carbamate